Truly interactive websites: an eye tracking approach - Zotos, Yorgos; Palla, Polyxeni; Tsiotsou, Rodoula H. (My University, 2014)
Designing effective websites remains a challenging task for both academics and practitioners. Attention is the starting point of any further cognitive process. The present study makes an attempt to assess which elements in a website gain individuals’ attention by measuring actual behavior instead of self-reported data. An online experiment was conducted and an eyetracking system was employed in order to track users’ attention to three interactive versions of a website that present a high involvement product. Data analysis establishes that five out of six web characteristics proposed by Voorveld et al. (2011) increase the perceived interactivity. In addition, it is reinforced the notion that online users are goal-oriented for high involvement product, since they allocate increased attention to the informational text provided in the homepage, regardless of the website interactivity level. Useful insights are provided for online marketers and academics regarding the elements that make a website truly interactive.
Keywords: Interactive websites; Website; Individuals’ attention; Eyetracking system